"Hunger Games" vs. "Simulation Games" - Adina-Mirela Festeu (Research Aspects in Arts and Social Studies Vol. 2, 2022)
The simulation of reality is realized by reducing it to its component symbols. According to Jean Baudrillard (Simulacra and Simulation), simulated violence is more dangerous than real violence because it undermines the principle of reality and questions law and order. Nor do refer to cruelty anymore, but stumble under the convention of simulation in a ghostly revival of past referents. The present research aims to analyse the particularities of certain mappings of reality according to Baudrillard’s theory of simulacra and simulation, with application to Suzanne Collins’ The Hunger Games trilogy. The media discourse used as a pillar of the construction of fictional-dystopian worlds produced the extension of simulacra, based on an approach specific to this era and its literary genre: parody. The hypothesis on which this research project is based is the deconstruction of contemporary human identity subjected to excesses of violence and simulacra and at the same time in permanent desynchronization with any traditional frame of reference. The novelty of the research lies in its critique of/ interrogation of/ probing into the culture of vulnerability, of the technological super-flux that spills over, not only in a direct form into personal life, leaving man "empty" of his own individuality, but also indirectly, through art, literature and culture.